Non-Reciprocal Delay Based on Photon-Phonon Interactions on a Chip - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (2019 Conference on Lasers and Electro-Optics, CLEO 2019 - Proceedings, 2019)
We demonstrate a non-reciprocal delay scheme based on stimulated Brillouin scattering in a planar highly nonlinear waveguide. The bandwidth of this scheme approaches a GHz, has wide frequency tunability and scales linearly with data power.
CRIS-Team Scopus Importer:2021-06-29